ISLAM DI TENGAH MASYARAKAT MULTIKULTURAL INDONESIA (Studi Atas Konsep Multikultural Abdul aziz Sachedina) - Lutfatul Azizah; Purjatian Azhar (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
Islam entered in Indonesia is not the cultural void, but rich with cultures ancestors that ingrained as a basic color of Indonesian state. Then, Religion came into another color on the Unitary Republic of Indonesia. Therefore, Republic of Indonesian is a country rich in religion, culture, tradition, language, ethnicity and race. Contiguity between religion and culture will be the discussion section this time. Abdul aziz Sachedina one of the leaders of modern Islamic political thinkers who could color the political development of modern Islamic. Abdul aziz Sachedina invited to browse the existence of the Islamic religion in the public square level. Debate on whether Islam as a guidance or governance becomes important glasses to see the reality of social life of religious communities. The conflict in the name of religion into the wider community unrest. Therefore we are talkative to restore life to the problems of religion, the conflict would be returned to religion. But, reality of religion can not answer these problems, not because religion is not able to answer it. Explored further was not because religion is not able to answer it, but a spokes man for the religious who are not able to deliver the desired resolution by social reality. As a multicultural social reality is already there from the time of The Prophet Muhammad SAW, but tolerance of that era are still not able yet to translate the social conditions of citizen currently